Training on Using the Mendeley Application for MGMP Mathematics Teachers at Muhammadiyah Middle Schools in the Yogyakarta City Region - Andriyani; Nur Ika Pujiastuti; Tutik Shahidayanti; Eka Kevin Alghiffari; Suci Pangestuti; Nur Jannah (Indonesian Journal of Society Development, 2023)
This Prodamat activity aims to provide training on the use of the Mendeley application for Muhammadiyah Middle School teachers in the Yogyakarta City Regional Mathematics Subject Teachers' Conference (MGMP). The methods for implementing this Prodamat activity are socialization regarding the introduction of the Mendeley application regarding the features of the Mendeley application, training on the use of the Mendeley application, also evaluation regarding the effectiveness of training activities on motivation for preparing scientific papers and teacher abilities. The evaluation results show the effectiveness of the implementation of training on the use of the Mendeley application, which is indicated by the high assessment of the training participant teachers in terms of improving the quality of scientific writing, increasing understanding of the use of the Mendeley application, use of the Mendeley application, applicable training materials and interactive presentation of material